Higher clearance of hepatitis C virus infection in females compared with males. Issue 8 (24th January 2006) - Bakr, I; Rekacewicz, C; El Hosseiny, M; Ismail, S; El Daly, M; El-Kafrawy, S; Esmat, G; Hamid, M A; Mohamed, M K; Fontanet, A
Abstract : Background and aims: According to the literature, 14–46% of subjects clear hepatitis C virus (HCV) from blood after infection. Controversy exists about sex differences in HCV clearance rates. Patients and methods: We compared HCV clearance in males and females using data from a large population based study on HCV infection in Egypt. Definitions used in the paper were: cleared HCV infection (positive HCV antibody and negative HCV RNA test results) and chronic HCV infection (positive HCV antibody and positive HCV RNA test results). The study sample included 4720 village residents aged 18–65 years recruited through home based visits (n = 2425) or voluntary screening (n = 2295). Results: Overall, HCV antibody prevalence was 910/4720 (19.3% (95% confidence interval 18.2–20.4)). Of those with HCV antibodies (n = 910), 61.5% had chronic HCV infection. Compared with males, females were more likely to have cleared the virus (44.6% v 33.7%, respectively; p = 0.001). Control for age, schistosomiasis history, iatrogenic exposures, and sexual exposure to HCV did not alter the positive association between female sex and viral clearance. Conclusion: This study provides strong evidence in favour of a higher HCV clearance rate in females compared with males.